Distribution and genetic diversity of multi-drug-resistant Klebsiella pneumoniae at the human–animal–environment interface in Pakistan - Aslam, Bilal; Chaudhry, Tamoor Hamid; Arshad, Muhammad Imran; Muzammil, Saima; Siddique, Abu Baker; Yasmeen, Nafeesa; Khurshid, Mohsin; Amir, Afreenish; Salman, Muhammad; Rasool, Muhammad Hidayat; Xia, Xueshan; Baloch, Zulqarnain (Frontiers in Microbiology, 2022)
Klebsiella pneumoniae is ubiquitous and known to be a notorious pathogen of human, animal, and plant-based food. K. pneumoniae is a recognized trafficker of antibiotic resistance genes (ARGs) between and from different ecological niches. A total (n=775) of samples were collected from September 2017 to August 2019 from the human, animal, and environmental sources by applying the random convenient sampling technique. A total of 120 (15.7%) samples were confirmed as K. pneumoniae. The distribution of K. pneumoniae among humans, the environment, and animals was 17.1%, 12.38%, and 10% respectively. Isolates have shown significant resistance against all the subjected antibiotics agents except colistin. Antibiotic resistance genes (ARGs) profiling revealed that the highest percentage prevalence (67.5%) of blaCTX-M was estimated in the isolates, various carbapenem resistance genes that were found in the study were blaNDM-1 (43.3%), blaOXA-48 (38%), and (1.67 %) blaKPC-2. Overall, 21 distinct sequence types and 13 clonal complexes were found through the multi-locus sequence typing (MLST) analysis. Taking together, the distribution of multi-drug resistance (MDR) K. pneumoniae clones in the community and associated environment is alarming for the health care system of the country. Health policymakers should consider the role of all the integral parts of human, animal, and associated environment intently to cope with this serious public and animal health concern.